Sad man's nose: Emotion induction and olfactory perception - Flohr, Elena L R; Erwin, Elena; Croy, Ilona; Hummel, Thomas (Emotion (Washington, D.C.), 2017)
Emotional and olfactory processing is frequently shown to be closely linked both anatomically and functionally. Depression, a disease closely related to the emotional state of sadness, has been shown to be associated with a decrease in olfactory sensitivity. The present study focuses on the state of sadness in n = 31 healthy subjects in order to investigate the specific contribution of this affective state in the modulation of olfactory processing. A sad or indifferent affective state was induced using 2 movies that were presented on 2 separate days. Afterward, chemosensory-evoked potentials were recorded after stimulation with an unpleasant (hydrogen sulfide: "rotten eggs") or a pleasant (phenyl ethyl alcohol: "rose") odorant. Latencies of N1 and P2 peaks were longer after induction of the sad affective state. Additionally, amplitudes were lower in a sad affective state when being stimulated with the unpleasant odorant. Processing of olfactory input has thus been reduced under conditions of the sad affective state. We argue that the affective state per se could at least partially account for the reduced olfactory sensitivity in depressed patients. To our knowledge, the present study is the first to show influence of affective state on chemosensory event-related potentials. (PsycINFO Database Record